Komunikasi pada Komunitas dalam Mempertahankan Solidaritas Anggota - Moch Irham Fauzan; Maman Suherman (UNISBA Press, 2024)
Abstract. During the COVID-19 pandemic, cycling has become popular in Indonesia. According to a survey from The Institute for Transportation and Development (ITDP), bicycle users in Indonesia increased 10 times during the social restrictions (PSBB) imposed by the government. In the midst of this situation, the Rebo Kahiji Community emerged, which is a cycling group that operates on Wednesdays. This community was formed in 2020 during the pandemic and continues to exist until after the pandemic with various routine activities. Based on this phenomenon, the problems in this study are formulated as follows: (1) what is the theme of communication that occurs among members of the Rebo Kahiji community in maintaining solidarity? (2) What are the obstacles and efforts to overcome the obstacles of the Rebo Kahiji community in maintaining solidarity? (3) why the exchange of business information among members plays an important role in maintaining solidarity. The purpose of this research is to understand how communication in this community maintains solidarity, this research uses qualitative methods, constructivist paradigms and case study approaches, and applies George Homans' social exchange theory . The research subject is the head of the Rebo Kahiji community. The results of the study show that communication within this community includes sharing experiences, information on competitions and events, as well as exchanging business information. Even though there are obstacles, this community tries to overcome them with the active role of the chairman. There is also an exchange of business information that creates openness, mutual need, and sharing of benefits among community members. Abstrak. Selama pandemi COVID-19, bersepeda menjadi populer di Indonesia. Menurut survei dari The Institute for Transportation and Development (ITDP), pengguna sepeda di Indonesia meningkat 10 kali lipat selama pembatasan sosial (PSBB) yang diterapkan pemerintah. Di tengah situasi ini, muncul Komunitas Rebo Kahiji, merupakan kelompok bersepeda yang beraktifitas pada hari Rabu. Komunitas ini terbentuk pada tahun 2020 saat pandemi dan tetap eksis hingga pasca pandemi dengan berbagai kegiatan rutin. Berdasarkan fenomena tersebut, maka permasalahan dalam penelitian ini dirumuskan sebagai berikut: (1) bagaiman tema komunikasi yang terjadi pada anggota komunitas Rebo Kahiji dalam mempertahankan solidaritas? (2) Bagaimana hambatan komunitas rebo kahiji dan upaya mengatasi hambatan komunikasi dalam komunitas ? (3) mengapa pertukaran informasi bisnis kepada sesama anggota berperan penting dalam mempertahankan solidaritas.Tujuan penelitian ini adalah memahami bagaimana komunikasi dalam komunitas ini mempertahankan solidaritas, penelitian ini menggunakan dengan metode kualitatif, pendekatan studi kasus, serta teori pertukaran sosial George Homans. Subjek penelitian adalah ketua Komunitas Rebo Kahiji. Hasil penelitian menunjukkan bahwa komunikasi dalam komunitas ini mencakup berbagi pengalaman, informasi lomba dan acara, serta pertukaran informasi bisnis. Meskipun terdapat hambatan, komunitas ini berusaha mengatasi dengan peran aktif dari ketua. Terdapat pula pertukaran informasi bisnis yang menciptakan keterbukaan, saling membutuhkan, dan berbagi manfaat di antara anggota komunitas.